Ultrasonically-assisted production of biodiesel from waste cooking oil (WCO) - Mohd Radzi, Rozihad (2008)
The use and research of biodiesel from waste cooking oil as an alternative fuel for the diesel engine started because of the decrease of petroleum production by Organization of the Petroleum Exporting Countries (OPEC) and the resulting in price increase. Waste cooking oil (WCO) was selected as raw material for production of biodiesel because it is inexpensive and can save our environment from pollution. In this study, transesterification process assisted with ultrasonic was chosen as a process to produce biodiesel. It is the reaction of a fat or oil with methanol in presence of sodium hydroxide as catalyst to form methyl esters and glycerol. Effect of using ultrasonic was study on transesterification reaction time. The result, using ultrasonic was proved to be time and energy saving. The process of transesterification in this study is affected by reaction temperature, catalyst (sodium hydroxide) concentration and reaction time. Thin-layer chromatography (TLC) are used to study the formation of methyl esters of waste cooking oil in the reaction and Karl Fisher analyzer are used to study the moisture content in biodiesel. Base on this research, excess amount of catalyst (NaOH) and excess reaction time at higher temperature affects a negative impact on the ester yield, resulted in a reduction of the product yield. The optimum conditions to achieve the highest conversion and yield of biodiesel were using 1.5 wt % sodium hydroxide (NaOH) at reaction temperature 30ºC and reaction time of 20 minutes.